Educational Attainment, and Milk Production in the Kavrepalanchok District of Nepal - Regmi, Devraj (Nepal Journal of Multidisciplinary Research, 2022)
On July 28, 2016, the Nepali government recognized the Kavrepalanchok district to be the first in the nation to become self-sufficient in milk production. The study's main objective was to assess the educational status (Quality education) in the community of the Kavrepalanchok district based on a geographical perspective. Therefore, 400 dairy farmers were chosen using a straightforward random selection method. The study was based on both qualitative and quantitative data. Because 59.2 percent of respondents agreed that they could afford to pay for their child's education from the income of milk production. The majority of respondents were able to do so using the income from raising livestock. As a result, the vast majority of the respondent's economic development was extremely satisfying, and it was discovered that the Kavrepalanchok district was starting to reach the stage of access to technological progress.